Penguatan Spiritualitas dan Komitmen Pelayanan Anggota Baru Legio Maria - tandiangga, patrio (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
This PkM activity aims to strengthen the spirituality and commitment to service of all new members of the Legion of Mary in the North Toraja region. The implementation of PkM activities for the Legion of Mary includes two methods, namely a participatory and reflective approach with four stages of implementation, namely: procurement of handbooks, mentoring weekly meetings, recollection and pilgrimage activities, and inauguration and inauguration of the presidium. The procurement of handbooks is intended to help new members of the Legion of Mary understand their identity, duties, and values ​​lived as a legionary. Furthermore, the mentoring of weekly meetings aims to improve technical understanding of meeting procedures along with the arrangement of meeting agendas and Discipline in carrying out tasks. The next activity is to carry out recollection and pilgrimage activities for the legionaries. Recollection and pilgrimage aim to strengthen spiritual experience and deepen devotion to Mother Mary as an exemplary figure. Furthermore, the pronouncement of the oath and inauguration of legionaries and officers is intended to strengthen the commitment of the legionaries to become loyal soldiers of Mother Mary in carrying out the duties of the apostolic work. The results of the implementation of PkM activities show an increase in active participation, spiritual maturity, and structural readiness in carrying out apostolic work. Thus, this PkM activity has succeeded in forming a strong spiritual and organizational foundation for the development of the Legion of Mary in North Toraja.